THE EFFECT OF AMMONIA CONCENTRATION AND TENSILE STRESS IN STRESS CORROSION CRACKING OF UNS C71500 (70CU- 30NI) MATERIAL USING IMMERSION METHOD - Nadya Laurenza P, Vincensi
70Copper-30Nickel alloys are materials with high corrosion resistance and are frequently used as heat exchanger tube. However, this materials is susceptible to stress corrosion cracking failure in ammonie environment. This final project is inspired by the failure of heat exchanger tube at PT. Chandra Asri due to stress corrosion cracking. The damages were caused by ammonia from dissolution of hydrazine oxygen scavengers which were used to decrease the oxygen level in water. A 15-day corrosion test of UNS C71500 materials with immersion method in ammonia solutions with concentrations of 3, 5, and 7M together with tensile stress applied from c-ring method (ASTM G38) with 100, 120, and 140% of yield strength varation were used in this research. The results were pitting and intergranular corrosion of C71500 materials but stress corrosion cracking was absent. The corrosion rates were determined from the mass difference of the specimens before and after corrosion test and the results showed that there is no effect of tensile stress variations on corrosion rate. The average corrosion rates of C71500 materials for ammonia concentration of 3, 5, and 7M are 0,525, 0,252, and 0,380 mm/year. It can be concluded that C71500 materials which had been corrosion tested in ammonia solutions with immersion and c-ring method for 15 days did not show any sign of stress corrosion cracking but pitting and intergranular corrosions.